High-energy and high-safety pole piece battery cell structure as well as preparation method and application thereof
By designing a high-energy density battery electrode plate structure, including setting up a multi-layer material structure in the positive and negative electrode plates, the problem of insufficient safety of the battery under extreme conditions is solved, and the effect of significantly improving battery safety under the premise of high energy density is achieved.
Patent Information
- Application Number
- CN202510077918.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-17
AI Technical Summary
Existing batteries are prone to safety problems such as fire and explosion in extreme temperatures, overcharging, fast charging or mechanical damage, and lack thermal stability and safety.
By designing a structure of a positive electrode and negative electrode sheet with high energy density, including setting up a lithium-rich manganese base layer, a high nickel ternary layer, a lithium manganese ferrophosphate layer and a nanoceramic layer in the positive electrode sheet from bottom to top, and setting up a natural graphite coating, a metal lithium foil layer and a fast-charging graphite layer in the negative electrode sheet from bottom to top, ensuring that the safety of the battery is not affected under extreme conditions such as high temperature, fast charging, and high SOC.
On the premise of ensuring high energy density, the safety of the battery is significantly improved, avoiding safety problems such as thermal runaway, fire or explosion under extreme conditions such as high temperature, fast charging, and high SOC, extending the service life of the battery, and meeting the applications of high energy needs such as electric vehicles and energy storage equipment.
Smart Images

Figure CN119890397A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and in particular to a high-energy, high-safety pole piece battery cell structure and a preparation method and application thereof. Background Art
[0002] With the rapid development of electric vehicles, energy storage devices, and wearable electronic devices, higher requirements are placed on battery energy density and safety. At present, there is still a certain contradiction between energy density and safety in battery technology. Although many batteries have improved their energy density by improving electrode materials (such as high-nickel ternary materials and metallic lithium), their thermal stability and safety still have major hidden dangers, especially in extreme temperatures (such as high temperature environments), overcharging, fast charging, or mechanical damage. Fire, explosion and other safety issues are prone to occur. Therefore, how to ensure the high energy density of the battery while improving its safety has become a key issue in current battery technology research.
[0003] In view of this, this application is hereby filed. Summary of the invention
[0004] The problem with the prior art is that the thermal stability and safety of the current battery still have great hidden dangers, especially under extreme temperatures, overcharging, fast charging or mechanical damage, it is easy to cause safety problems such as fire and explosion. The present invention provides a high-energy, high-safety electrode cell structure and a preparation method and application. Through the design of positive and negative electrode materials and structures, it can significantly improve the safety of the battery while ensuring high energy density, especially under extreme conditions such as high temperature, fast charging, high SOC, etc., to ensure that the safety of the battery is not affected.
[0005] The present invention is achieved through the following technical solutions:
[0006] In a first aspect, the present invention provides a high-energy, high-safety electrode cell structure, including a positive electrode and a negative electrode;
[0007] The positive electrode sheet comprises a positive electrode substrate, on which a lithium-rich manganese base layer, a high-nickel ternary layer, a lithium iron manganese phosphate layer and a nano-ceramic layer are sequentially arranged from bottom to top;
[0008] The negative electrode plate comprises a negative electrode substrate, on which a natural graphite coating, a metal lithium foil layer and a fast-charging graphite layer are sequentially arranged from bottom to top.
[0009] The present invention can significantly improve the safety of the battery while ensuring high energy density (≥400Wh / kg) through the design of positive and negative electrode materials and structures, especially under extreme conditions such as high temperature, fast charging, and high SOC, to ensure that the safety of the battery is not affected.
[0010] In a specific embodiment, the positive electrode substrate adopts an ultra-thin carbon-coated aluminum foil current collector, and the thickness of the ultra-thin carbon-coated aluminum foil current collector is 7-9 μm.
[0011] In the present invention, the positive electrode plate includes five layered structures, and the bottom layer adopts an ultra-thin carbon-coated aluminum foil current collector material with a thickness of 7-9 μm as a substrate, which has excellent conductivity and mechanical strength and can ensure efficient transmission of current in the battery.
[0012] In a specific embodiment, the lithium-rich manganese base layer is made of Li2MnO3, LiMnO2 or Li 1.12 Mn 1.88 O4, or other lithium-rich manganese materials, the thickness of the lithium-rich manganese base layer is 30-50 μm.
[0013] In the present invention, a lithium-rich manganese-based material is coated on the carbon-coated aluminum foil as the inner layer of the positive electrode plate. The material has a relatively high gram-specific capacity (250-270 mAh / g), but its extremely low conductivity will affect its capacity. Therefore, coating a 30-50 μm thick lithium-rich manganese-based material on the bottom carbon-coated aluminum foil layer can effectively increase the contact area between the material and the current collector and improve its conductivity.
[0014] The specific ratio of the lithium-rich manganese-based layer is: commercial lithium-rich manganese-based layer: PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 95.0%: 1.2%: 1.5%: 2.3%.
[0015] In a specific embodiment, the high nickel ternary layer is made of NCM811, Ni 72 Co5Mn 13 or Ni 85 Co5Mn 10 , or other high-nickel ternary materials, the thickness of the high-nickel ternary layer is 80-150μm.
[0016] In the present invention, the middle layer of the positive electrode plate adopts high-nickel ternary material, which has high capacity, high voltage platform and good cycle performance. The coating thickness is 80-150μm, which can significantly improve the energy density and rate performance of the battery.
[0017] The specific ratio of the high-nickel ternary layer is commercial high-nickel ternary (811): PVDF: SP (conductive carbon black) = 97.0%: 1.5%: 1.5%.
[0018] In a specific embodiment, the lithium manganese iron phosphate layer is made of LiMnFePO4, LiMn 0.5 Fe 0.5 PO4 or LiMn 0.8 Fe 0.2PO4, or other lithium manganese iron phosphate materials, the thickness of the lithium manganese iron phosphate layer is 10-30 μm.
[0019] In the present invention, the outer layer of the positive electrode plate is made of lithium iron manganese phosphate (such as LiMnFePO4) material with a coating thickness of 10-30μm, which has good thermal stability and safety. This material can not only ensure the stability of the battery under high temperature and high SOC, but also prevent thermal runaway during overheating and overcharging, thereby ensuring the safety of the battery under abnormal conditions.
[0020] The specific ratio of the lithium manganese iron phosphate layer is commercial lithium manganese iron phosphate (LMFP): PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 95.5%: 1.0%: 1.5%: 2.0%.
[0021] In a specific embodiment, the nano-ceramic layer is made of Al2O3 or SiO2 nano-material, and the thickness of the nano-ceramic layer is 3-5 μm.
[0022] In the present invention, a nano-ceramic layer with a thickness of 3-5 μm is added to the outermost layer of the positive electrode plate, and high temperature resistant nano-materials such as Al2O3 or SiO2 are used. This layer can effectively block heat transfer and prevent heat diffusion when the battery is overcharged or an abnormality occurs inside, thus avoiding thermal runaway of the battery. Nano-ceramic materials are not only lightweight, but also have excellent chemical resistance and heat insulation properties, further improving the safety of the battery.
[0023] The specific ratio of the nano ceramic layer is commercial nano aluminum oxide or silicon oxide (Al2O3 / SiO2): PVDF=35%:65%.
[0024] In a specific embodiment, the negative electrode substrate is made of ultra-thin copper foil, and the thickness of the ultra-thin copper foil is ≤4 μm.
[0025] In the present invention, the negative electrode plate includes four layered structures. The bottom layer uses ultra-thin copper foil (≤4μm) as a conductive substrate with high conductivity and mechanical strength. The use of ultra-thin copper foil reduces the mass and volume of the copper foil and also improves the thermal conductivity of the battery. In addition, ultra-thin copper foil helps the battery to dissipate heat more effectively, reduce the temperature inside the battery, and avoid overheating that has a negative impact on battery life and safety. At the same time, the improvement of thermal management performance makes the battery more stable under high power and fast charging conditions, avoiding the risk of thermal runaway of the battery.
[0026] In a specific embodiment, the natural graphite coating is made of natural graphite material with a particle size D50 of 15-20 μm, and the thickness of the natural graphite coating is 20-50 μm.
[0027] In the present invention, a natural graphite layer with a thickness of 20-50 μm is coated on the surface of the copper foil. The natural graphite not only has a low cost but also has good conductivity and stability. It is used as a transition layer between the metal lithium foil and the current collector, which can effectively improve the bonding performance of the lithium foil, guide lithium ions to deposit toward the inner layer during the charge and discharge process, and alleviate the extreme growth of lithium dendrites toward the outer layer and pierce the diaphragm to cause thermal runaway to a certain extent.
[0028] In a specific embodiment, the metal lithium foil layer is a metal lithium foil with a thickness of 10-20 μm.
[0029] In the present invention, a 10-20 μm thick metal lithium foil is rolled and coated on a natural graphite layer. Metal lithium is a negative electrode material with the highest specific capacity (3860 mAh / g), which can significantly increase the energy density of the battery. The specific capacity of the negative electrode can be significantly increased by designing the metal lithium foil layer. The specific ratio of the natural graphite layer is commercial natural graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black) = 98.0%: 1.0%: 1.0%.
[0030] In a specific embodiment, the fast-filling graphite layer is made of a fast-filling graphite material with a particle size D50 of 5-10 μm, and the thickness of the fast-filling graphite layer is 10-20 μm.
[0031] In the present invention, a 10-20 μm fast-charging graphite layer is finally rolled and coated on the metal lithium foil, which can effectively improve the deintercalation of surface lithium ions, improve the stability of the battery during high-rate charging, reduce internal resistance, and avoid lithium ions from aggregating and precipitating in the outer layer, causing capacity decay and safety problems. The specific ratio of the fast-charging graphite layer is commercial fast-charging graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 96.0%: 1.0%: 1.0%: 2.0%.
[0032] In a second aspect, the present invention provides a method for preparing a high-energy, high-safety electrode core structure, comprising the following steps:
[0033] (1) uniformly coating a natural graphite material on a negative electrode substrate and vacuum drying to obtain a natural graphite coating;
[0034] (2) rolling and compounding a layer of metal lithium foil on the natural graphite coating to obtain a metal lithium foil layer;
[0035] (3) uniformly coating the fast-charging graphite material on the metal lithium foil layer and vacuum drying to obtain a negative electrode sheet;
[0036] (4) uniformly coating the lithium-rich manganese-based material on the positive electrode substrate and vacuum drying to obtain a lithium-rich manganese-based layer;
[0037] (5) uniformly coating the high-nickel ternary material on the lithium-manganese-rich base layer, and vacuum drying to obtain a high-nickel ternary layer;
[0038] (6) uniformly coating the lithium iron manganese phosphate material on the high nickel ternary layer, and vacuum drying to obtain a lithium iron manganese phosphate layer;
[0039] (7) uniformly coating the nano-ceramic material on the lithium manganese iron phosphate layer and vacuum drying to obtain a positive electrode sheet;
[0040] (8) The negative electrode sheet and the positive electrode sheet are stacked to form a battery cell.
[0041] In a third aspect, the present invention provides an application of a high-energy, high-safety electrode cell structure in a battery.
[0042] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0043] 1. The embodiment of the present invention provides a high-energy, high-safety electrode cell structure, a preparation method and an application thereof. By designing the positive electrode and negative electrode materials and structures, the safety of the battery can be significantly improved while ensuring high energy density, especially under extreme conditions such as high temperature, fast charging and high SOC, to ensure that the safety of the battery is not affected;
[0044] 2. The embodiment of the present invention provides a high-energy, high-safety electrode cell structure, preparation method and application, which adopts innovative negative and positive electrode materials and structural design, so that the energy density of the cell can reach more than 400Wh / kg, and the thermal runaway temperature is increased to more than 160°C, which can meet the high energy demand applications such as electric vehicles and energy storage equipment;
[0045] 3. The embodiment of the present invention provides a high-energy, high-safety electrode cell structure, preparation method and application, which greatly improves the thermal stability, mechanical strength and safety of the battery through the gradient design of the positive and negative electrode structures, and effectively avoids safety problems such as thermal runaway, fire or explosion under extreme conditions such as high temperature, high SOC or acupuncture;
[0046] 4. The embodiment of the present invention provides a high-energy, high-safety electrode cell structure, a preparation method and an application thereof, which improves the cycle performance of the battery and prolongs the service life of the battery by rationally selecting the electrode material combination and optimizing the gradient coating thickness of the electrode;
[0047] 5. The high-energy, high-safety electrode cell structure, preparation method and application provided in the embodiments of the present invention are suitable for power batteries (such as electric vehicles), energy storage systems and high-power application fields, especially for lithium battery systems with high energy and high safety requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0049] Figure 1 A schematic diagram of the negative electrode plate structure design provided by an embodiment of the present invention;
[0050] Figure 2 A schematic diagram of the positive electrode plate structure design provided in an embodiment of the present invention. DETAILED DESCRIPTION
[0051] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments and drawings. The exemplary embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.
[0052] In the following description, a large number of specific details are set forth in order to provide a thorough understanding of the present invention. However, it is apparent to one of ordinary skill in the art that these specific details need not be employed to practice the present invention. In other embodiments, in order to avoid obscuring the present invention, well-known materials or methods are not specifically described.
[0053] Throughout the specification, references to "one embodiment," "an embodiment," "an example," or "an example" mean that a particular feature, structure, or characteristic described in conjunction with the embodiment or example is included in at least one embodiment of the present invention. Therefore, the phrases "one embodiment," "an embodiment," "an example," or "an example" appearing in various places throughout the specification do not necessarily all refer to the same embodiment or example. In addition, particular features, structures, or characteristics may be combined in one or more embodiments or examples in any suitable combination and / or subcombination. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0054] Example 1
[0055] like Figure 1 and Figure 2 As shown, an embodiment of the present invention provides a method for preparing a high-energy and high-safety electrode cell structure, comprising the following steps:
[0056] (1) Mixing natural graphite negative electrode material in a mass ratio of commercial natural graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black) = 98.0%: 1.0%: 1.0%, putting the mixture into a stirring tank for homogenization at a stirring speed of 30 rpm for 20 min to obtain slurry A;
[0057] (2) Slurry A was evenly coated on a 4 μm copper foil with a coating scraper to a coating thickness of 40 μm, and then placed in a vacuum drying oven and baked at 60° C. for 2 h to obtain electrode A;
[0058] (3) placing the electrode A in a glove box and using a small roller to roll and laminate a layer of 20 μm metal lithium foil on the coating to obtain the electrode B;
[0059] (4) Mix the fast-charging graphite negative electrode material according to the mass ratio of commercial fast-charging graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 96.0%: 1.0%: 1.0%: 2.0%, put it into a stirring tank for mixing and homogenization, and stir at a speed of 50 rpm for 30 minutes to obtain slurry B;
[0060] (5) Slurry B was evenly coated on the electrode B using a coating scraper in a glove box, with a coating thickness of 10 μm, and then transferred to a vacuum drying oven and baked at 45° C. for 0.5 h to obtain a negative electrode C, with an overall electrode thickness of about 75 μm;
[0061] (6) Mixing the commercial lithium-rich manganese-based positive electrode material in a mass ratio of 95.0%: 1.2%: 1.5%: 2.3% of PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) and putting the mixture into a stirring tank for homogenization at a stirring speed of 60 rpm for 50 min to obtain slurry C;
[0062] (7) Slurry C was evenly coated on a 7 μm carbon-coated aluminum foil with a coating blade to a coating thickness of 50 μm, and then placed in a vacuum drying oven and baked at 100° C. for 2 h to obtain electrode D;
[0063] (8) mixing high nickel ternary positive electrode materials in a mass ratio of commercial high nickel ternary (811): PVDF: SP (conductive carbon black) = 97.0%: 1.5%: 1.5%, putting the mixture into a stirring tank for mixing and homogenization, stirring at a speed of 60 rpm for 50 min to obtain slurry D;
[0064] (9) Slurry D was evenly coated on the electrode D with a coating scraper to a coating thickness of 100 μm, and then placed in a vacuum drying oven and baked at 80° C. for 2 h to obtain electrode E;
[0065] (10) Mixing lithium manganese iron phosphate positive electrode material according to the mass ratio of commercial lithium manganese iron phosphate (LMFP): PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 95.5%: 1.0%: 1.5%: 2.0%, putting into a stirring tank for mixing and homogenization, stirring at a speed of 100 rpm for 120 min to obtain slurry E;
[0066] (11) Slurry E is evenly coated on electrode E with a coating scraper to a coating thickness of 10 μm, and then placed in a vacuum drying oven and baked at 60° C. for 1 h to obtain electrode F;
[0067] (12) mixing nano-ceramic materials in a mass ratio of commercial nano-alumina (Al2O3) to PVDF = 35% to 65%, and putting the mixture into a stirring tank for homogenization at a stirring speed of 200 rpm for 30 min to obtain slurry F;
[0068] (13) Slurry F was evenly coated on the electrode E with a coating scraper to a coating thickness of 5 μm, and then placed in a vacuum drying oven and baked at 100°C for 1 h to obtain a positive electrode G with an overall thickness of about 172 μm;
[0069] (14) The negative electrode plate C and the positive electrode plate G were stacked in a glove box to form a battery cell. The separator used a 7 μm base film, double-sided ceramic double-sided tape, and a 1+1 μm coating on both sides. After packaging with a 60 μm aluminum-plastic film, the electrolyte was injected with DMC:EMC:EC=1:1:1. After injection, the battery was left to stand for 48 hours. After completion, the electrochemical performance test was started.
[0070] Example 2
[0071] The embodiment of the present invention provides a method for preparing a high-energy and high-safety electrode cell structure, comprising the following steps:
[0072] (1) Mixing natural graphite negative electrode material in a mass ratio of commercial natural graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black) = 98.0%: 1.0%: 1.0%, putting the mixture into a stirring tank for homogenization at a stirring speed of 30 rpm for 20 min to obtain slurry A;
[0073] (2) Slurry A was evenly coated on a 4 μm copper foil with a coating scraper to a coating thickness of 50 μm, and then placed in a vacuum drying oven and baked at 60° C. for 2 h to obtain electrode A;
[0074] (3) Placing the electrode A in a glove box and using a small roller to roll and laminate a layer of 15 μm metal lithium foil on the coating to obtain the electrode B;
[0075] (4) Mix the fast-charging graphite negative electrode material according to the mass ratio of commercial fast-charging graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 96.0%: 1.0%: 1.0%: 2.0%, put it into a stirring tank for mixing and homogenization, and stir at a speed of 50 rpm for 30 minutes to obtain slurry B;
[0076] (5) Slurry B was evenly coated on the electrode B using a coating scraper in a glove box, with a coating thickness of 15 μm, and then transferred to a vacuum drying oven and baked at 45° C. for 0.5 h to obtain a negative electrode C, with an overall electrode thickness of about 85 μm;
[0077] (6) Mixing the commercial lithium-rich manganese-based positive electrode material in a mass ratio of 95.0%: 1.2%: 1.5%: 2.3% of PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) and putting the mixture into a stirring tank for homogenization at a stirring speed of 60 rpm for 50 min to obtain slurry C;
[0078] (7) Slurry C was evenly coated on a 7 μm carbon-coated aluminum foil with a coating blade to a coating thickness of 50 μm, and then placed in a vacuum drying oven and baked at 100° C. for 2 h to obtain electrode D;
[0079] (8) mixing high nickel ternary positive electrode materials in a mass ratio of commercial high nickel ternary (811): PVDF: SP (conductive carbon black) = 97.0%: 1.5%: 1.5%, putting the mixture into a stirring tank for mixing and homogenization, stirring at a speed of 60 rpm for 50 min to obtain slurry D;
[0080] (9) Slurry D was evenly coated on the electrode D with a coating scraper to a coating thickness of 100 μm, and then placed in a vacuum drying oven and baked at 80° C. for 2 h to obtain electrode E;
[0081] (10) Mixing lithium manganese iron phosphate positive electrode material according to the mass ratio of commercial lithium manganese iron phosphate (LMFP): PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 95.5%: 1.0%: 1.5%: 2.0%, putting into a stirring tank for mixing and homogenization, stirring at a speed of 100 rpm for 120 min to obtain slurry E;
[0082] (11) Slurry E is evenly coated on electrode E with a coating scraper to a coating thickness of 10 μm, and then placed in a vacuum drying oven and baked at 60° C. for 1 h to obtain electrode F;
[0083] (12) mixing nano-ceramic materials in a mass ratio of commercial nano-alumina (Al2O3) to PVDF = 35% to 65%, and putting the mixture into a stirring tank for homogenization at a stirring speed of 200 rpm for 30 min to obtain slurry F;
[0084] (13) Slurry F was evenly coated on the electrode E with a coating scraper to a coating thickness of 5 μm, and then placed in a vacuum drying oven and baked at 100°C for 1 h to obtain a positive electrode G with an overall thickness of about 172 μm;
[0085] (14) The negative electrode plate C and the positive electrode plate G were stacked in a glove box to form a battery cell. The separator used a 7 μm base film, double-sided ceramic double-sided tape, and a 1+1 μm coating on both sides. After packaging with a 60 μm aluminum-plastic film, the electrolyte was injected with DMC:EMC:EC=1:1:1. After injection, the battery was left to stand for 48 hours. After completion, the electrochemical performance test was started.
[0086] Example 3
[0087] The embodiment of the present invention provides a method for preparing a high-energy and high-safety electrode cell structure, comprising the following steps:
[0088] (1) Mixing natural graphite negative electrode material in a mass ratio of commercial natural graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black) = 98.0%: 1.0%: 1.0%, putting the mixture into a stirring tank for homogenization at a stirring speed of 30 rpm for 20 min to obtain slurry A;
[0089] (2) Slurry A was evenly coated on a 4 μm copper foil with a coating scraper to a coating thickness of 30 μm, and then placed in a vacuum drying oven and baked at 60° C. for 2 h to obtain electrode A;
[0090] (3) placing the electrode A in a glove box and using a small roller to roll and laminate a layer of 20 μm metal lithium foil on the coating to obtain the electrode B;
[0091] (4) Mix the fast-charging graphite negative electrode material according to the mass ratio of commercial fast-charging graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 96.0%: 1.0%: 1.0%: 2.0%, put it into a stirring tank for mixing and homogenization, and stir at a speed of 50 rpm for 30 minutes to obtain slurry B;
[0092] (5) Slurry B was evenly coated on the electrode B using a coating scraper in a glove box, with a coating thickness of 20 μm, and then transferred to a vacuum drying oven and baked at 45° C. for 0.5 h to obtain a negative electrode C, with an overall electrode thickness of about 75 μm;
[0093] (6) Mixing the commercial lithium-rich manganese-based positive electrode material in a mass ratio of 95.0%: 1.2%: 1.5%: 2.3% of PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) and putting the mixture into a stirring tank for homogenization at a stirring speed of 60 rpm for 50 min to obtain slurry C;
[0094] (7) Slurry C was evenly coated on a 7 μm carbon-coated aluminum foil with a coating blade to a coating thickness of 50 μm, and then placed in a vacuum drying oven and baked at 100° C. for 2 h to obtain electrode D;
[0095] (8) mixing high nickel ternary positive electrode materials in a mass ratio of commercial high nickel ternary (811): PVDF: SP (conductive carbon black) = 97.0%: 1.5%: 1.5%, putting the mixture into a stirring tank for mixing and homogenization, stirring at a speed of 60 rpm for 50 min to obtain slurry D;
[0096] (9) Slurry D was evenly coated on the electrode D with a coating scraper to a coating thickness of 100 μm, and then placed in a vacuum drying oven and baked at 80° C. for 2 h to obtain electrode E;
[0097] (10) Mixing lithium manganese iron phosphate positive electrode material according to the mass ratio of commercial lithium manganese iron phosphate (LMFP): PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 95.5%: 1.0%: 1.5%: 2.0%, putting into a stirring tank for mixing and homogenization, stirring at a speed of 100 rpm for 120 min to obtain slurry E;
[0098] (11) Slurry E is evenly coated on electrode E with a coating scraper to a coating thickness of 10 μm, and then placed in a vacuum drying oven and baked at 60° C. for 1 h to obtain electrode F;
[0099] (12) mixing nano-ceramic materials in a mass ratio of commercial nano-alumina (Al2O3) to PVDF = 35% to 65%, and putting the mixture into a stirring tank for homogenization at a stirring speed of 200 rpm for 30 min to obtain slurry F;
[0100] (13) Slurry F was evenly coated on the electrode E with a coating scraper to a coating thickness of 5 μm, and then placed in a vacuum drying oven and baked at 100°C for 1 h to obtain a positive electrode G with an overall thickness of about 172 μm;
[0101] (14) The negative electrode plate C and the positive electrode plate G were stacked in a glove box to form a battery cell. The separator used a 7 μm base film, double-sided ceramic double-sided tape, and a 1+1 μm coating on both sides. After packaging with a 60 μm aluminum-plastic film, the electrolyte was injected with DMC:EMC:EC=1:1:1. After injection, the battery was left to stand for 48 hours. After completion, the electrochemical performance test was started.
[0102] Example 4
[0103] The embodiment of the present invention provides a method for preparing a high-energy and high-safety electrode cell structure, comprising the following steps:
[0104] (1) Mixing natural graphite negative electrode material in a mass ratio of commercial natural graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black) = 98.0%: 1.0%: 1.0%, putting the mixture into a stirring tank for homogenization at a stirring speed of 30 rpm for 20 min to obtain slurry A;
[0105] (2) Slurry A was evenly coated on a 4 μm copper foil with a coating scraper to a coating thickness of 40 μm, and then placed in a vacuum drying oven and baked at 60° C. for 2 h to obtain electrode A;
[0106] (3) placing the electrode A in a glove box and using a small roller to roll and laminate a layer of 20 μm metal lithium foil on the coating to obtain the electrode B;
[0107] (4) Mix the fast-charging graphite negative electrode material according to the mass ratio of commercial fast-charging graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 96.0%: 1.0%: 1.0%: 2.0%, put it into a stirring tank for mixing and homogenization, and stir at a speed of 50 rpm for 30 minutes to obtain slurry B;
[0108] (5) Slurry B was evenly coated on the electrode B using a coating scraper in a glove box, with a coating thickness of 10 μm, and then transferred to a vacuum drying oven and baked at 45° C. for 0.5 h to obtain a negative electrode C, with an overall electrode thickness of about 75 μm;
[0109] (6) Mixing the commercial lithium-rich manganese-based positive electrode material in a mass ratio of 95.0%: 1.2%: 1.5%: 2.3% of PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) and putting the mixture into a stirring tank for homogenization at a stirring speed of 60 rpm for 50 min to obtain slurry C;
[0110] (7) Slurry C was evenly coated on a 7 μm carbon-coated aluminum foil with a coating blade to a coating thickness of 40 μm, and then placed in a vacuum drying oven and baked at 100° C. for 2 h to obtain electrode D;
[0111] (8) mixing high nickel ternary positive electrode materials in a mass ratio of commercial high nickel ternary (811): PVDF: SP (conductive carbon black) = 97.0%: 1.5%: 1.5%, putting the mixture into a stirring tank for mixing and homogenization, stirring at a speed of 60 rpm for 50 min to obtain slurry D;
[0112] (9) Slurry D was evenly coated on the electrode D with a coating scraper to a coating thickness of 120 μm, and then placed in a vacuum drying oven and baked at 80° C. for 2 h to obtain electrode E;
[0113] (10) Mixing lithium manganese iron phosphate positive electrode material according to the mass ratio of commercial lithium manganese iron phosphate (LMFP): PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 95.5%: 1.0%: 1.5%: 2.0%, putting into a stirring tank for mixing and homogenization, stirring at a speed of 100 rpm for 120 min to obtain slurry E;
[0114] (11) Slurry E is evenly coated on electrode E with a coating scraper to a coating thickness of 20 μm, and then placed in a vacuum drying oven and baked at 60° C. for 1 h to obtain electrode F;
[0115] (12) mixing nano-ceramic materials in a mass ratio of commercial nano-alumina (Al2O3) to PVDF = 35% to 65%, and putting the mixture into a stirring tank for homogenization at a stirring speed of 200 rpm for 30 min to obtain slurry F;
[0116] (13) Slurry F was evenly coated on the electrode E with a coating scraper to a coating thickness of 5 μm, and then placed in a vacuum drying oven and baked at 100° C. for 1 h to obtain a positive electrode G with an overall thickness of 192 μm;
[0117] (14) The negative electrode plate C and the positive electrode plate G were stacked in a glove box to form a battery cell. The separator used a 7 μm base film, double-sided ceramic double-sided tape, and a 1+1 μm coating on both sides. After packaging with a 60 μm aluminum-plastic film, the electrolyte was injected with DMC:EMC:EC=1:1:1. After injection, the battery was left to stand for 48 hours. After completion, the electrochemical performance test was started.
[0118] Example 5
[0119] The embodiment of the present invention provides a method for preparing a high-energy and high-safety electrode cell structure, comprising the following steps:
[0120] (1) Mixing natural graphite negative electrode material in a mass ratio of commercial natural graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black) = 98.0%: 1.0%: 1.0%, putting the mixture into a stirring tank for homogenization at a stirring speed of 30 rpm for 20 min to obtain slurry A;
[0121] (2) Slurry A was evenly coated on a 4 μm copper foil with a coating scraper to a coating thickness of 40 μm, and then placed in a vacuum drying oven and baked at 60° C. for 2 h to obtain electrode A;
[0122] (3) placing the electrode A in a glove box and using a small roller to roll and laminate a layer of 20 μm metal lithium foil on the coating to obtain the electrode B;
[0123] (4) Mix the fast-charging graphite negative electrode material according to the mass ratio of commercial fast-charging graphite: CMC (carboxymethyl cellulose): SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 96.0%: 1.0%: 1.0%: 2.0%, put it into a stirring tank for mixing and homogenization, and stir at a speed of 50 rpm for 30 minutes to obtain slurry B;
[0124] (5) Slurry B was evenly coated on the electrode B using a coating scraper in a glove box, with a coating thickness of 10 μm, and then transferred to a vacuum drying oven and baked at 45° C. for 0.5 h to obtain a negative electrode C, with an overall electrode thickness of about 75 μm;
[0125] (6) Mixing the commercial lithium-rich manganese-based positive electrode material in a mass ratio of 95.0%: 1.2%: 1.5%: 2.3% of PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) and putting the mixture into a stirring tank for homogenization at a stirring speed of 60 rpm for 50 min to obtain slurry C;
[0126] (7) Slurry C was evenly coated on a 7 μm carbon-coated aluminum foil with a coating blade to a coating thickness of 30 μm, and then placed in a vacuum drying oven and baked at 100° C. for 2 h to obtain electrode D;
[0127] (8) mixing high nickel ternary positive electrode materials in a mass ratio of commercial high nickel ternary (811): PVDF: SP (conductive carbon black) = 97.0%: 1.5%: 1.5%, putting the mixture into a stirring tank for mixing and homogenization, stirring at a speed of 60 rpm for 50 min to obtain slurry D;
[0128] (9) Slurry D was evenly coated on the electrode D with a coating scraper to a coating thickness of 150 μm, and then placed in a vacuum drying oven and baked at 80° C. for 2 h to obtain electrode E;
[0129] (10) Mixing lithium manganese iron phosphate positive electrode material according to the mass ratio of commercial lithium manganese iron phosphate (LMFP): PVDF: SP (conductive carbon black): SCNT (single-walled carbon nanotube) = 95.5%: 1.0%: 1.5%: 2.0%, putting into a stirring tank for mixing and homogenization, stirring at a speed of 100 rpm for 120 min to obtain slurry E;
[0130] (11) Slurry E was evenly coated on the electrode E with a coating scraper to a coating thickness of 30 μm, and then placed in a vacuum drying oven and baked at 60° C. for 1 h to obtain electrode F;
[0131] (12) mixing nano-ceramic materials in a mass ratio of commercial nano-alumina (Al2O3) to PVDF = 35% to 65%, and putting the mixture into a stirring tank for homogenization at a stirring speed of 200 rpm for 30 min to obtain slurry F;
[0132] (13) Slurry F was evenly coated on the electrode E with a coating scraper to a coating thickness of 5 μm, and then placed in a vacuum drying oven and baked at 100°C for 1 h to obtain a positive electrode G with an overall thickness of 222 μm;
[0133] (14) The negative electrode plate C and the positive electrode plate G were stacked in a glove box to form a battery cell. The separator used a 7 μm base film, double-sided ceramic double-sided tape, and a 1+1 μm coating on both sides. After packaging with a 60 μm aluminum-plastic film, the electrolyte was injected with DMC:EMC:EC=1:1:1. After injection, the battery was left to stand for 48 hours. After completion, the electrochemical performance test was started.
[0134] Comparative Example 1
[0135] This comparative example provides a method for preparing a pole piece battery cell structure, which is different from Example 1 in that the negative pole piece adopts a commercial natural graphite pole piece with a thickness of 75 μm.
[0136] Comparative Example 2
[0137] This comparative example provides a method for preparing a pole piece battery cell structure, which is different from Example 1 in that a negative pole piece adopts a metal lithium foil pole piece with a thickness of 75 μm.
[0138] Comparative Example 3
[0139] This comparative example provides a method for preparing a pole piece battery cell structure, which is different from Example 1 in that a commercial fast-charging graphite pole piece is used as the negative pole piece, and the pole piece thickness is 75 μm.
[0140] Comparative Example 4
[0141] This comparative example provides a method for preparing a pole piece battery cell structure, which is different from Example 1 in that: the positive pole piece adopts a commercial R&F manganese lithium pole piece with a thickness of 160 μm.
[0142] Comparative Example 5
[0143] This comparative example provides a method for preparing a pole piece battery cell structure, which is different from Example 1 in that a commercial high-nickel ternary pole piece is used as the positive pole piece, and the pole piece thickness is 160 μm.
[0144] Comparative Example 6
[0145] This comparative example provides a method for preparing a pole piece battery cell structure, which is different from Example 1 in that a commercial lithium manganese iron phosphate ternary pole piece is used as the positive pole piece, and the pole piece thickness is 160 μm.
[0146] The materials prepared in Examples 1-5 and Comparative Examples 1-6 were made into button batteries and their electrical performance was tested. The data are shown in Table 1 below.
[0147] Table 1
[0148]
[0149] It can be seen from the data in Table 1 that the electrode cell structure provided in Examples 1-5 of the present invention has high energy density, good battery cycle performance, good thermal stability, and will not cause safety problems such as thermal runaway, fire or explosion in a high temperature environment, and has high safety. Comparative Examples 1 to 3 use the same positive electrode plate as Example 1, and the negative electrode plate uses a single-component plate. It can be seen that its energy density is lower than that of Example 1. Although Comparative Example 2 has a high energy density, its cycle performance and safety are very poor. Comparative Examples 4 to 6 use the same negative electrode plate as Example 1, and the positive electrode plate uses a single-component plate. Its energy density and cycle performance are lower than that of Example 1 as a whole. Although Comparative Example 4 has a high energy density, its cycle performance and safety are also very poor. Although Comparative Example 6 has high safety, its energy density is low and it is difficult to meet battery requirements.
[0150] In summary, the present invention adopts innovative negative and positive electrode materials and structural designs, as well as an optimized design of the gradient coating thickness of the pole piece, so that the energy density of the battery cell can reach more than 400Wh / kg, and the thermal runaway temperature is increased to more than 160°C. Under the premise of ensuring high energy density, the thermal stability, mechanical strength and safety of the battery can be greatly improved, especially under extreme conditions such as high temperature, fast charging, and high SOC. The safety of the battery is not affected, and safety problems such as thermal runaway, fire or explosion under extreme conditions such as high temperature, high SOC or acupuncture are effectively avoided, the battery cycle performance is improved, and the battery service life is extended; it can meet the high energy demand applications such as electric vehicles, energy storage equipment and high power, and is particularly suitable for lithium battery systems with high energy and high safety requirements.
[0151] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A high-energy, high-safety electrode cell structure, comprising a positive electrode and a negative electrode; characterized in that: The positive electrode sheet comprises a positive electrode substrate, on which a lithium-rich manganese base layer, a high-nickel ternary layer, a lithium iron manganese phosphate layer and a nano-ceramic layer are sequentially arranged from bottom to top; The negative electrode plate comprises a negative electrode substrate, on which a natural graphite coating, a metal lithium foil layer and a fast-charging graphite layer are sequentially arranged from bottom to top.
2. A high-energy, high-safety electrode core structure according to claim 1, characterized in that: The positive electrode substrate adopts an ultra-thin carbon-coated aluminum foil current collector, and the thickness of the ultra-thin carbon-coated aluminum foil current collector is 7-9 μm.
3. The high-energy, high-safety electrode core structure according to claim 1, characterized in that: The lithium-rich manganese base layer is made of Li2MnO3, LiMnO2 or Li 1.12 Mn 1.88 O4, the thickness of the lithium-rich manganese base layer is 30-50 μm.
4. The high-energy, high-safety electrode core structure according to claim 1, characterized in that: The high nickel ternary layer is made of NCM811, Ni 72 Co5Mn 13 or Ni 85 Co5Mn 10 , the thickness of the high nickel ternary layer is 80-150 μm.
5. The high-energy, high-safety electrode core structure according to claim 1, characterized in that: The lithium manganese iron phosphate layer is made of LiMnFePO4, LiMn 0.5 Fe 0.5 PO4 or LiMn 0.8 Fe 0.2 PO4, the thickness of the lithium manganese iron phosphate layer is 10-30 μm.
6. The high-energy, high-safety electrode core structure according to claim 1, characterized in that: The nano ceramic layer is made of Al2O3 or SiO2 nano material, and the thickness of the nano ceramic layer is 3-5 μm.
7. The high-energy, high-safety electrode core structure according to claim 1, characterized in that: The negative electrode substrate is made of ultra-thin copper foil, and the thickness of the ultra-thin copper foil is ≤4 μm.
8. The high-energy, high-safety electrode core structure according to claim 1, characterized in that: The natural graphite coating is made of natural graphite material with a particle size D50 of 15-20 μm, and the thickness of the natural graphite coating is 20-50 μm.
9. The high-energy, high-safety electrode core structure according to claim 1, characterized in that: The metal lithium foil layer is a metal lithium foil with a thickness of 10-20 μm.
10. The high-energy, high-safety electrode core structure according to claim 1, characterized in that: The fast-filling graphite layer is made of a fast-filling graphite material with a particle size D50 of 5-10 μm, and the thickness of the fast-filling graphite layer is 10-20 μm.
11. The method for preparing the high-energy and high-safety electrode core structure according to any one of claims 1 to 10, characterized in that: The steps include: (1) uniformly coating a natural graphite material on a negative electrode substrate and vacuum drying to obtain a natural graphite coating; (2) rolling and compounding a layer of metal lithium foil on the natural graphite coating to obtain a metal lithium foil layer; (3) uniformly coating the fast-charging graphite material on the metal lithium foil layer and vacuum drying to obtain a negative electrode sheet; (4) uniformly coating the lithium-rich manganese-based material on the positive electrode substrate and vacuum drying to obtain a lithium-rich manganese-based layer; (5) uniformly coating the high-nickel ternary material on the lithium-manganese-rich base layer, and vacuum drying to obtain a high-nickel ternary layer; (6) uniformly coating the lithium iron manganese phosphate material on the high nickel ternary layer, and vacuum drying to obtain a lithium iron manganese phosphate layer; (7) uniformly coating the nano-ceramic material on the lithium manganese iron phosphate layer and vacuum drying to obtain a positive electrode sheet; (8) The negative electrode sheet and the positive electrode sheet are stacked to form a battery cell.
12. Application of the high-energy, high-safety electrode cell structure according to any one of claims 1 to 10 in a battery.
Citation Information
Patent Citations
Lithium ion battery
CN107482166A
Gradient potential distribution negative electrode, a lithium ion battery and a preparation method and application of the lithium ion battery
CN113113568A
Preparation method of multi-layer composite electrode and lithium ion battery of multi-layer composite electrode
CN115020642A
Positive plate and battery comprising same
CN115939318A
Pole piece and preparation method and application thereof
CN117199235A